Influence of Ningbo–Zhoushan Port Main Corridor on the Tidal Current Dynamics in the Zhoushan Sea Area - Zhanxiong Gu (Geofluids, 2022)
Ningbo–Zhoushan Port Main Corridor project is important in the development of Zhoushan City, but its impact on the hydrodynamic characteristics of the Zhoushan sea area is still unclear. Finite volume method is used in the present study to solve the shallow water equations and establish a plane two-dimensional tidal current numerical model. The measured tidal current data of the Yangtze River Estuary and Hangzhou Bay is utilized to verify the accuracy of the model in simulating the tidal current process. The results indicate the model can numerically reproduce the tidal current process in the Hangzhou Bay–Yangtze River Estuary–Zhoushan sea area (HYZ). In addition, the dynamic characteristics of tidal currents in the Zhoushan sea area with and without piers are compared. The results show that the construction of the project changes the water level near the bridge piers and causes the water obstruction and deficiency in the front and behind the piers, respectively. Tidal flow velocity increases on sides of the piers with while a low velocity area is formed before and after the piers. The project construction exerts a small impact on the tidal currents but a strong influence on the local area near the bridge piers.